USING OF GEOINFORMATION TECHNOLOGIES IN ASSESSMENT OF QUALITY CONDITION OF ROADS (World Science, 2021)
The article presents a method for assessing the quality of roads using geographic information technologies to create digital models of the road and the surrounding area. The construction of such digital models is performed on the basis of geospatial coordinates to be processed during the certification of roads. When processing data in specialized software packages, geometric parameters and indicators of compliance with traffic safety conditions are obtained on the basis of spatial coordinates. Based on the constructed digital models, the indicators of functional wear are estimated.